2015
DOI: 10.1371/journal.pone.0135370
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy Improves Hemostatic and Liver Functions in Hepatosplenic Schistosomiasis Mansoni

Abstract: BackgroundSchistosomiasis mansoni is a chronic liver disease, in which some patients (5–10%) progress to the most severe form, hepatosplenic schistosomiasis. This form is associated with portal hypertension and splenomegaly, and often episodes of gastrointestinal bleeding, even with liver function preserved. Splenectomy is a validated procedure to reduce portal hypertension following digestive bleeding. Here, we evaluate beneficial effects of splenectomy on blood coagulation factors and liver function tests in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
3
19
0
1
Order By: Relevance
“…Morais et al (25) showed that this enzyme as an accurate marker to predict moderate and severe fibrosis in patients with hepatitis C. With regard to schistosomiasis, a study described by Leite et al (18) with 55 hepatosplenic patients, they found the prevalence of advanced fibrosis in 54.5% of patients and compared them to healthy individuals, the levels of AP presented significantly elevated (P<0.0001). Other studies with hepatosplenic patients, they showed a significant increase in serum levels of AP in relation to control groups (19,20) . In schistosomiasis, the changes of the intrahepatic biliary tree, either by ductal injuries caused by ovular reactions or arising from of PPF, could be the anatomical substrate for the increase of this enzyme (3,34) .…”
Section: Characteristics Of the Patientsmentioning
confidence: 79%
“…Morais et al (25) showed that this enzyme as an accurate marker to predict moderate and severe fibrosis in patients with hepatitis C. With regard to schistosomiasis, a study described by Leite et al (18) with 55 hepatosplenic patients, they found the prevalence of advanced fibrosis in 54.5% of patients and compared them to healthy individuals, the levels of AP presented significantly elevated (P<0.0001). Other studies with hepatosplenic patients, they showed a significant increase in serum levels of AP in relation to control groups (19,20) . In schistosomiasis, the changes of the intrahepatic biliary tree, either by ductal injuries caused by ovular reactions or arising from of PPF, could be the anatomical substrate for the increase of this enzyme (3,34) .…”
Section: Characteristics Of the Patientsmentioning
confidence: 79%
“…Several studies have found that splenectomy could improve liver function among patients with Child grade B liver function. 22,24,37 In our research, hepatic function in most patients was ameliorated 1 year after surgery, especially among patients who underwent splenectomy. One possible factor contributes this effect is that these patients received additional medical treatments or changed their lifestyles, such as antiviral therapy, smoking cessation, and alcohol withdrawal.…”
Section: Discussionmentioning
confidence: 52%
“…21 Several studies reported that patients with Child B liver function benefited from splenectomy, and liver function in most patients improved significantly 1 year after splenectomy. [22][23][24] Other studies also indicated that splenectomy combined with hepatectomy could extend disease-free survival and overall survival. 12,15,25 However, these studies had some limitations, with either small sample sizes or heterogeneous populations.…”
Section: Introductionmentioning
confidence: 99%
“…Complications due to splenomegaly are mainly related to mechanical symptoms (pain, early satiety, diarrhoea and distension), portal hypertension, and splenic sequestration with exacerbation of previous cytopenias. [38][39][40] The use of ruxolitinib has contributed to reduce splenectomy for treatment of myelofibrosis. However, in thrombocytopenia (<20×103/uL) or cytopenias associated with use of ruxolitinib, splenectomy is indicated and has proven beneficial.…”
Section: Myelofibrosismentioning
confidence: 99%